Primer of biostatistics - Glantz, Stanton A. (McGraw-Hill, Medical Pub. Div., 2011)
The new fifth edition of Primer of Biostatistics introduces this challenging topic in a readable and enjoyable format that assumes no prior knowledge of the subject. In no time, you'll understand test selection and be able to evaluate biomedical statistics critically and knowledgably.